Prolonged QT Syndrome and Seizure Secondary to Alkaline Earth Metal Deficiency: A Case Report - A. McKinney; B. C. Keegan (Case Reports in Medicine)
Introduction. Alkaline earth metal deficiency is recognized as a cause of both seizure and long QT syndrome. Their deficiency can have significant repercussions on the function of cells, tissues, and organs of the body. An understanding of the role of electrolytes allows an appreciation of the significance of depleted levels on cell function. Case Report. A 65-year-old lady was admitted with symptoms of chest discomfort, vomiting, increased stoma output, and dizziness. Two days following admission she suffered a tonic-clonic seizure. ECG review demonstrated a prolonged QTc interval, raising the possibility of an underlying Torsades de Pointes as the precipitant. This was attributed to electrolyte disturbance arising as a result of multiple aetiologies. Discussion. This paper highlights the multisystem effects of electrolyte disturbance, with emphasis upon its role in precipitating cardiac arrhythmia and neurological symptoms.